THE EFFECT OF ZAKAT AND ISLAMIC CORPORATE SOCIAL RESPONSIBILITY (ICSR) ON COMPANY PERFORMANCE (Empirical Study of Sharia Commercial Banks Listed on the Indonesia Stock Exchange on 2013-2017) - Eva Fauziah Ahmad (Indonesian Journal Of Business And Economics, 2019)
The aims of the Research is to examine the influence of zakat and Islamic Corporate Social Responsibility (ICSR) about effort of the companies in Sharia public banks enrolled on the Indonesia Stock Exchange in 2013-2017The method of the Research are used descriptive analysis techniques and verificative analysis. The population of the Research were 12 Sharia Retail Bank that has been enrolled on the Indonesia Stock Exchange in 2013-2017. The sample of this Research were 8 Islamic Commercial Banks multiplied by 5 years observation into 40 sample data, and the technique were used purposive sampling. The analytical instrument are used multiple regression analysis with the help of SPSS version 21.0The Results are showed that partially zakat had an effect on effort of the company, while ICSR had no effect on it. Simultaneous test shows that zakat and ICSR have an effect on effort of the company.